Does terror increase aid? - Dreher, Axel; Fuchs, Andreas (Public choice, 2011)
This article investigates empirically whether, and in what ways, donors in the Development Assistance Committee respond to transnational terrorist incidents and the onset of the War on Terror by changing aid effort and aid allocation. First, an analysis of 22 donor countries shows that aid effort increased during the War on Terror period, but did not respond to the actual number of terror events. Second, using aid allocation equations, we find that countries where terror originates are not more likely to receive aid as a consequence, but if they are selected, they receive larger amounts of aid. Our results imply that politicians may still have to learn from economic research. To the extent that development aid can effectively combat terror across the world, as recent research suggests it does, politicians would be well-advised to target aid to those countries where terrorist groups exist in abundance.